The Validation of Go-Lab Based Inquiry Learning Spaces (ILS) on Science Subject for Junior High School Student - Fuad Tamami; Joni Rokhmat; Ahmad Harjono (Jurnal Penelitian Pendidikan IPA, 2022)
Learning innovation in the midst of a situation like now needs to be done to adapt to the times. The times require teachers to continue to innovate by modernizing learning activities to suit the interests of students. The purpose of this research is to produce a learning innovation by combining inquiry learning and the use of information technology called Inquiry Learning Spaces (ILS) based on Go-Lab. The method used in this development research is 4D which has the stages of Define, Design, Develop, and Disseminate. This research will focus on the first three stages: Define, Design, Develop. At the Develop stage, validation is carried out on the product being developed. Validation was carried out by 3 experts in the fields of Physics Education, Media, and Learning Technology. Product reliability is also carried out using a percentage of agreement. From the results of expert validation, it was found that the product developed had an average score percentage of 88.31% with a very valid category. In addition, the percentage of agreement results show that each instrument's percentage has a value above 75% in the reliable category. Several criticisms and suggestions from the validator became a significant improvement to improve the Inquiry Learning Spaces (ILS) which was developed so that it could be used in science learning in junior high schools.